Development of electronic voting machine with the inclusion of near field communication ID cards, biometric fingerprint sensor and POS printer - Anis, Arafa Mohd.; Rahman, Hamidur; Alam, Jennifer Sherry; Nabil, Sohel Islam; Hasan, Syed Mahmud (BRAC University, 2015)
Cataloged from PDF version of thesis report.